An Update on Access to Novel Treatment for Metastatic Melanoma in Europe — A 2024 Survey of the European Melanoma Registry and the European Association of Dermato-Oncology - Kandolf, L; Ascierto, P; Bastholt, L; Gavrilova, I; Haanen, J; Hauschild, A; Herceg, D; Hoeller, C; Jalovcic Suljevic, A; Kessels, JI; Krajsova, I; Kukushkina, M; et al. (Elsevier BV, 2024)
Advances in cancer treatments have significantly improved their effectiveness, yet access to first-line therapies remains limited. A 2017 survey revealed that over 25% of metastatic melanoma patients in Europe lacked access to recommended therapies. To address this, the European Association of Dermato-Oncology and the European Melanoma Registry conducted a follow-up study on the registration and reimbursement of first-line treatments.A web-based survey using LimeSurvey was distributed to melanoma experts across 27 European countries from February to April 2022 and updated from February to April 2024. The questionnaire covered the percentage of patients receiving recommended treatments, as well as treatment authorization and reimbursement dates for systemic and adjuvant therapies.There has been significant improvement in the registration and reimbursement of BRAFi/MEKi, anti-PD1, and anti-PD1/anti-CTLA4 therapies, increasing from 48%, 63%, and 37% in 2017 to 96%, 96%, and 78% in 2024, respectively. Despite these gains, restrictions persist. Anti-PD1/anti-CTLA4 combination immunotherapy is still not available without restrictions in 48% of the surveyed countries. The nivolumab/relatlimab combination is licensed only for PDL-1-negative melanoma and reimbursed in seven countries of Europe. Tebentafusp is reimbursed in 12 countries and talimogene laherpervec in 6. In 2024, adjuvant treatments for stage III melanoma are reimbursed in 22 countries for dabrafenib/trametinib and 24 of 27 for anti-PD1 antibodies. Pembrolizumab and nivolumab are reimbursed in 16 and 8 countries, respectively, for stage IIB/IIC disease.While there have been improvements in the reimbursement of metastatic melanoma treatments in Europe, challenges and discrepancies remain. Further efforts at European and global levels are needed to harmonize and enhance access to cancer medicines.
Keywords: melanoma; access to medicines; disparities; cancer care; immunotherapy; targeted therapy